Effect of Citric and Acetic Acid Supplementation in Drinking Water on Broiler Growth Performance Under Hot Climate Conditions - Abdul Hadi Erfan; Hazrat Ali Ishaq; Noor Aminullah (Journal of Applied Veterinary Science And Technology, 2026)
Background: Hot climate condition remains a challenge that impact gut health leading to enteritis, which results growth suppression in poultry. Other hand, to maintain the gut health and support growth performance, antimicrobials are being used which accompanied with multidrug microbial resistance development.  Purpose:  This experiment was aimed to evaluate the effect of citric and acetic acids added acidifier drinking water on broiler growth performance under hot climate condition. Method: Total of 135 one day old ross 308 broiler chicks were procured, kept under a deep litter production system and randomly assigned to five experimental groups: “C” as control received normal tap water, T1 received 0.5% citric acid, T2 1% citric acid, T3 0.5% acetic acid, and T4 received 1% acetic acid in drinking water thorough the experiment. Experimental group was divided into 3 replicates containing 9 chicks each. Results:  Body weight gain (BWG) and feed conversion ratio (FCR) were depressed (p<0.05) from day 1 to 7th, while BWG and FCR both improved (p<0.05) from day 7 to 21st in T3 & T4 groups. During finisher phase (from day 21st to 42nd), the 1% citric acid addition to the drinking water improved (p<0.05) FCR. Cumulative BWG, daily weight gain (DWG) and FCR also were better (p<0.05) at 1% citric acid supplemented level which demonstrated 100% survivability compared to control, whereas acetic acid had no effect during finisher phase. Cumulative FI, European Production Efficiency Factor (EPEF) and European Broiler Index (EBI) remained unaffected among the treatment groups. Conclusion: Experimental demonstrated that acetic acid enhanced chick growth performance during the starter phase, whereas citric acid exhibited a superior effect across the entire production cycle.